Hukum Waris Islam Dipandang Dari Perspektif Hukum Berkeadilan Gender - Maryati Bachtiar (Fakultas Hukum Universitas Riau, 2012)
As state which its resident majority believe in Islamenabled by a lot of society member using Islam punishsystem. But along with the times marked by tech-nological advances and the principles of Islamic lawcontinues to progress rapidly and always follow thechanging times in order to benefit people in the world.Without differentiating woman and men. frombreakdown of the solution can pulled a conclusion thathereditary law of Islam have accomodated lawprinciple which with justice gender.